Review Article:Ἤπειρόνδε. Proceedings of the 10th International Symposium of Byzantine Sigillography (Ioannina, 1-3 October 2009), eds. CHRISTOS STAVRAKOS and BARBARA PAPADOPOULOU, Wiesbaden: Harrassowitz Verlag, 2011 (360 p.). - KARAGIORGOU, Olga (Byzantina Symmeikta, 2016)
Review Article:Ἤπειρόνδε. Proceedings of the 10th International Symposium of Byzantine Sigillography (Ioannina, 1-3 October 2009), eds. Christos Stavrakos and Barbara Papadopoulou, Wiesbaden: Harrassowitz Verlag, 2011 (360 p.).